Integration of Problem-Based Learning and Student Worksheets Improves Junior High School Scientific Literacy: A Systematic Literature Review - Fitri Muslihatun; Diyah Nurmayanti; Elya Suci Nabila; Fitria Herawadini (Indonesian Publication Center, 2026)
The low level of scientific literacy among junior high school students remains a major challenge in 21st-century science education, particularly in connecting scientific concepts with real-life phenomena. This study employs a Systematic Literature Review (SLR) to identify the most effective patterns for integrating Problem-Based Learning (PBL) and Student Worksheets (LKPD) in improving students’ scientific literacy. The analysis was conducted on articles published between 2016 and 2025 obtained from Google Scholar, ERIC, and ScienceDirect with the help of the Publish or Perish application based on specific inclusion criteria. The findings indicate that the integration of PBL and LKPD consistently produces learning tools that are valid, practical, and effective, with improvements in scientific literacy ranging from moderate to high levels. The use of E-LKPD and contextual-based worksheets also enhances student engagement and supports skills in analysis, data interpretation, and scientific problem-solving. The effectiveness of this integration is influenced by the quality of LKPD design, the implementation of PBL syntax, and structured scaffolding. This study concludes that integrating PBL and LKPD becomes more optimal when supported by innovative learning materials and teachers’ readiness in facilitating problem-based learning. It implies the need to develop adaptive, interactive, and contextual LKPD to promote meaningful science learning and 21st-century skills.